Psychometric properties of the Headache Under-Response to Treatment (HURT) questionnaire and the Migraine Disability Assessment Test (MIDAS) translated to Serbian - Zivkovic Zaric, Radica; Jankovic, Slobodan M; Csépány, Éva; Gyüre, Tamás; Ertsey, Csaba; Andjelkovic, Marija (Vojnosanitetski pregled, 2021)
Abstract Background/Aim. The Headache Under-Response to Treatment (HURT) questionnaire and the Migraine Disability Assessment Test (MIDAS), which are intended for assessing the headache-related disability, impact (MIDAS) and management (HURT), were not yet translated to Serbian and validated in the population of Serbia. The aim of this study was to translate the HURT and MIDAS from English to Serbian, to make necessary cultural adaptations and to test their psychometric properties in a sample of outpatients with the headache. Methods. The HURT and MIDAS questionnaires were translated and adapted according to the internationally accepted guidelines, and then tested on a sample of Serbian patients with various headache types. Internal consistency was checked through the calculation of Cronbach’s alpha for the questionnaires, and by correlation of each question with the corrected total score. The criterion validity of the translation was tested by correlating scores of individual items, domains and whole questionnaire with the headache characteristics (severity, duration, frequency), and convergent validity was tested by correlating the abovementioned scores with results of an instrument for measurement of headache-related quality of life. Results. There were 171 (79.2%) females and 45 (20.8%) male study participants. The mean age of the patients was 42.3 years, (standard deviation – SD 13.35; range 18–75); 27 (12.5%) suffered from a migraine and 189 (87.5%) from the episodic tension-type headache (TTH). The Serbian translation of HURT and MIDAS questionneires showed excellent internal consistency, with high values of the Cronbach’s alpha: 0.764 and 0.731, respectively. The validity of the instruments in all aspects (criterion, convergent and discriminant validity) was also excellent for the whole sample and for the subgroup of patients with TTH, while the results for the patients with the migraine were less favorable. The factor analysis suggested the existence of one domain of MIDAS and two domains of HURT questionneires. Conclusion. The Serbian translations of HURT and MIDAS could be used as the reliable and valid specific instruments for measuring a headache-related disability, impact (MIDAS) and management (HURT) in the patients with TTH and probably in the patients with the migraine.
Keywords: headache; migraine disorders; analgesics; treatment outcome; serbia; translating; surveys and questionnaires